(untitled) (Carte Romanze, 2015)
Il saggio presenta una nuova edizione critica delle tre poesie attribuite dagli studiosi ad Arnaut de Tintinhac, preceduta da un’ampia introduzione. Dallo studio della tradizione manoscritta dei testi, delle attribuzioni contrastanti, della toponomastica e della lingua si arriva a mettere in dubbio la paternità delle tre liriche o la loro attribuzione a un medesimo autore. The essay proposes a new critical edition of three poems which are attributed by the scholars to Arnaut de Tintinhac; a wide introduction precedes the editions. The analysis of the manuscript tradition, the contrasting attributions, the judgement of the historical toponymy and language cast doubt on the authorship of these poems or their ascription to a single author.